If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 39 = -6x + 5(3x + -12) Reorder the terms: 39 = -6x + 5(-12 + 3x) 39 = -6x + (-12 * 5 + 3x * 5) 39 = -6x + (-60 + 15x) Reorder the terms: 39 = -60 + -6x + 15x Combine like terms: -6x + 15x = 9x 39 = -60 + 9x Solving 39 = -60 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 39 + -9x = -60 + 9x + -9x Combine like terms: 9x + -9x = 0 39 + -9x = -60 + 0 39 + -9x = -60 Add '-39' to each side of the equation. 39 + -39 + -9x = -60 + -39 Combine like terms: 39 + -39 = 0 0 + -9x = -60 + -39 -9x = -60 + -39 Combine like terms: -60 + -39 = -99 -9x = -99 Divide each side by '-9'. x = 11 Simplifying x = 11
| 14-6x=4-4x | | -4x+5(-x-18)=-36 | | 32=2(4)+4(2h)+4(2h) | | .05n+.1D=1.60 | | 13x^10+143x^9+715x^8+2145x^7+4290x^6+6006x^5+6006x^4+4290x^3+2145x^2+715x+130=300 | | -0.15x+x=1 | | -15=-5x+2(3x-2) | | L=L(r+R) | | 13x^11+143x^10+715x^9+2145x^8+4290x^7+6006x^6+6006x^5+4290x^4+2145x^3+715x^2+130x=300 | | X/2×(x-3)=90 | | 6/w=42 | | F=L(r+R)forR | | .80+1=.75+2 | | 284=2x+5(6x-20) | | 71x-7x=5x-13 | | 13+e=3 | | .50x+13=.75x+15 | | (1/27)^(4-x)=9^(2x−1) | | -8-7(-5-5v+1v)= | | 2x-5/6=-4/5 | | (3x-5)/(5x^2) | | 9(4x+7)= | | X=(-3/-4)*12 | | X+(x-7)=8 | | X^4+13x^2+1= | | 2(-3a+5)=(a+4) | | 3x4/5y | | 6-3(2y+5)=-4y+6-y | | 7x+5=12x-0 | | 6.3*10^15/2.1*10^11 | | 32=8+8h+8h | | 2m+8=22 |